Ḥusn al-Jawāb ‘an Ithbāt al-Ahillah bi al-Ḥisāb: Basyūnī ‘Imrān’s Method for Standardising the Determination of the Qamariyah Month in the Sultanate of Sambas (1913-1976) - Herlambang, Saifuddin; Rizqina, Aulia Laily; Ridwansyah, Ridwansyah; Muslih, Moh.; Naffati, Abdel Kadir (Journal of Islamic Law, 2024)
This article analyses the responses of Basyūnī ‘Imrān (1885-1976), a muftī (jurisconsult) and qādhī (judge) with the title Mahārāja Imām (highest religious official) in the Sambas Sultanate, to the debates surrounding the determination of the beginning of Ramaḍān and Eid al-Fitr at the turn of the twentieth century. The differences arose from conflicting claims of accuracy between two methods, ḥisāb (astronomical calculations) and ruʾyah (physical sighting of the moon), in determining the start of the lunar month among Muslims. Concerned about these issues, Basyūnī ‘Imrān addressed them in his manuscript written in Arabic-Malay (known as Aksara Jawī), titled Ḥusn al-Jawāb ‘an Ithbāt al-Ahillah bi al-Ḥisāb (1933). By employing a historical approach and content analysis of the manuscript, the authors find that Basyūnī ‘Imrān favoured the ḥisāb method for determining the start of the lunar month. In addition to referencing Sūrah al-Raḥmān verse 5, Sūrah Yūnus verse 5, and a hadith narrated by Imām Mālik, Basyūnī ‘Imrān also considered the geographical and social conditions of Muslims to standardise the observance of fasting and Islamic festivals in the Sultanate of Sambas and its surroundings. He argued that differences in determining the start of the lunar month should not lead to divisions among Muslims, as both methods are grounded in the same theological principles. This finding contributes to the history of Islamic legal thought in Indonesia by providing evidence of scholarly efforts to standardise the determination of the lunar month during his tenure as Mahārāja Imām in the Sultanate of Sambas from 1913 to 1976. [Artikel ini menganalisis respons Basyūnī ‘Imrān (1885-1976), muftī dan qādhī yang bergelar Mahārāja Imām di Kesultanan Sambas, terhadap polemik perbedaan dalam penentuan awal puasa Ramadhan dan hari raya Idul Fitri pada awal abad kedua puluh. Perbedaan tersebut disebabkan saling klaim kebenaran metode, antara ḥisāb dan ruʾyah, dalam penentuan awal bulan Qomariyah di kalangan umat Islam. Prihatin terhadap peristiwa tersebut, Basyūnī ‘Imrān meresponsnya sebagaimana yang tertuang dalam manuskrip berbahasa Arab-Melayu (dikenal sebagai Aksara Jawī) yang berjudul, Ḥusn al-Jawāb ‘an Ithbāt al-Ahillah bi al-Ḥisāb (1933). Dengan menggunakan pendekatan sejarah dan analisis konten manuskrip, para penulis menemukan bahwa Basyūnī ‘Imrān cenderung menggunakan metode ḥisāb dalam penentuan awal bulan Qomariyah. Selain merujuk pada Sūrah al-Raḥmān ayat 5, Sūrah Yūnus ayat 5, dan sebuah hadis yang diriwayatkan oleh Imām Mālik, Basyūnī ‘Imrān juga mempertimbangkan kondisi geografis dan sosial umat Islam untuk menyeragamkan pelaksanaan ibadah puasa dan hari raya Islam di Kesultanan Sambas dan sekitarnya. Menurutnya, perbedaan dalam penentuan awal bulan tersebut tidak boleh menimbulkan perpecahan di antara umat Islam, karena kedua metode tersebut berlandaskan pada dasar teologi yang sama. Temuan ini berkontribusi terhadap sejarah pemikiran hukum Islam di Indonesia dengan memberikan bukti adanya pemikiran ulama yang berupaya menyeragamkan penentuan awal bulan Qomariyah yang diterapkannya ketika menjabat sebagai Mahārāja Imām di Kesultanan Sambas pada tahun 1913 sampai 1976.]